Green-synthesized Zinc Oxide Nanoparticles from Cissus aralioides: Characterization, and Antimicrobial Potentials - Onunkwo, Innocent Chukwujekwu; Edema, Mary Olire; Ogwuche, Christiana E.; Akpeji, Bamidele H. (Sciences of Phytochemistry, 2026)
Antimicrobial resistance represents a critical global challenge due to microbial enzymes that neutralize antibiotic efficacy, prompting the use of nanotechnology to enhance the therapeutic potential of plant properties. In this study, zinc oxide nanoparticles (ZnONPs) were biosynthesized using a methanol extract of Cissus aralioides leaves obtained through Soxhlet extraction. Characterization via UV-vis, FTIR, PXRD, SEM, EDX, and TEM revealed a maximum absorption at 398 nm, a bandgap energy of 3.12 eV, and a hexagonal wurtzite structure with an average particle size of 15.90 ± 2.81 nm. FTIR analysis confirmed essential chemical groups (C-H, C=O, O-H), while SEM and EDX showed rough surfaces with a predominant zinc content of 80.76%. The antimicrobial potential of these ZnONPs was evaluated against Escherichia coli, Staphylococcus aureus, Aspergillus fumigatus, and Candida albicans using the agar well diffusion method at concentrations of 100–400 mg/mL. Results demonstrated significant antimicrobial activity, with the highest sensitivity observed against S. aureus (24.0 ± 0.01 mm), followed by C. albicans, E. coli, and Aspergillus sp., and an estimated minimum inhibitory concentration of 100–300 mg/mL. Consequently, this research highlights the potential of green-synthesized ZnONPs as a viable alternative for managing pathogenic microorganisms.